DIREITO À EDUCAÇÃO: UMA REFLEXÃO SOBRE METODISMO, INDUSTRIALIZAÇÃO E CLASSES POPULARES - SILVA, LUIZ EDUARDO PRATES DA (2017)
The purpose of this thesis is the discussion of the right to education, grounded on the principle that is by the word that humans come to be autonomous and conscious beings. Education is fundamental to word criticality, assuring its autonomy and consciousness. To deny the right to education is the denial of the critical word and, therefore, the denial of the humanity of the human beings. The demand for rights are made only by people who have been excluded from them; those already included in such rights do not demand them. Therefore, in the societies with high levels of social inequalities, only those people of the oppressed and exploited social classes demand for rights, i.e., the popular classes. Two historical contexts were studied in a diachronic comparison about the struggles for educational rights, having as reference the developments of the industrial capitalism in two different historical contexts: the 18th century England and Brazil’s first half of the 20th century. As in the prior moment to process of the English Industrial Revolution, the Methodist religious movement had considerable influence, with a high concern for the education of popular classes, this work discusses the foundations of such concern in the life and action of John Wesley, its founder, as well as its influence on the development of the new mode of production. The Brazilian process of industrialisation occurred two centuries later, creating different social demands, including the raising of the conscientization among sectors of the popular classes about the fundamental role of education in an industrial society. At the end of this thesis, from the analysis of both periods, we can perceive that, as much in the first historical context as well in the second, the right to education was in England and has been in Brazil denied to the popular classes. The right to education for the popular classes becomes a reality only through their struggles to ensure it.